Evaluation of DLC, MoS2, and Ti3C2Tx thin films for triboelectric nanogenerators. (15th June 2022) - Tremmel, Stephan; Luo, Xiongxin; Rothammer, Benedict; Seynstahl, Armin; Wang, Bo; Rosenkranz, Andreas; Marian, Max; Zhu, Laipan
Abstract: Due to their cost-effective fabrication, easy integration, and low frequency working range, triboelectric nanogenerators (TENGs) demonstrate tremendous potential in green energy harvesting to power smart devices and the internet of things (IoT). However, there is an urgent need to synergistically maximize their output and improve their durability to ensure a long-lasting high performance. This study aims at elucidating the performance of protective thin films deposited on the wear-prone PTFE surface of TENGs including doped and undoped, single- and multi-layer hydrogenated DLC films, MoS2 coatings fabricated by physical vapor deposition and multi-layer Ti3 C2 T x (MXene) films. The deposited coatings are characterized by electron microscopy, and Raman spectroscopy. Their triboelectric performance is analyzed for TENGs operating in contact separation and freestanding sliding modes. We verified that MXenes outperformed the other films in contact separation mode due to the good electron gain ability of functional oxygen and fluorine groups. In sliding mode, the undoped a-C:H coating performed on a comparable level to the uncoated reference and superior to the tungsten-doped DLC and MoS2 films. The film withstood long-term tests without notable signs of wear; merely the output slowly decreased with time due to graphitization and thus potential material transfer to the mating body. Graphical Abstract: ga1 Highlights: DLC, MoS2, and Ti3 C2 T x thin films were deposited on PTFE surface of TENGs. Triboelectric performance was studied in contact separation and sliding mode. Ti3 C2 T x thin films performed best in contact separation mode. Undoped DLC showed promising results in long-term sliding tests.